Theorizing the 'Third Sphere': A Critique of the Persistence of the 'Economistic Fallacy.' - Adaman, Fikret; Madra, Yahya M. (Journal of Economic Issues, 2002)
The paper seeks to investigate, from a methodological and ontological perspective, different ways of theorizing the third sphere–the set of activities that can be captured by neither the price mechanism of the markets nor by governmental transactions. The first aim is to elucidate the constitutive elements of the third sphere by deploying Polanyi's forms of integration (reciprocity, redistribution, and exchange). The second is to survey the ontologically individualist and methodologically formalist literature on the third sphere. After elucidating the coexisting sets of behavioral essences in contemporary ontologically individualist and methodologically formalist models of third-sphere activities, the paper claims that this proliferation of behavioral essences can only lead to a methodological impasse. The paper concludes that only with a committed recognition of the heterogeneity of the economy and the endogeneity of the economic subject will it become possible to better grasp the richness of third sphere activities.
Economics
Keywords: current heterodox approaches: institutional; economic methodology; economistic fallacy

The Contested Sovereignty of the Firm - Dietrich, Michael (Review of Political Economy, 2002)
This paper suggests that the firm can be analysed as a regulated system of contested sovereignty. The economic literature on the firm is categorised in terms of four different perspectives on sovereignty identified using the twin factors of power and authority. But rather than any single perspective being identified as analytically superior, it is argued that a system of contested sovereignty should be based on all four perspectives. Following this, a Polanyi-inspired analysis of firm regulation is presented in which the regulation of the firm emerges to control the costs of free markets. However, this regulation depicts firm sovereignty as complex and contested rather than simply an optimal response to market failures.
Economics
Keywords: business enterprises; economics and literature; firm regulation; firm sovereignty; political economy

Transnational Pharmaceutical Corporations and Neo-Liberal Business Ethics in India - D'Mello, Bernard (Journal of Business Ethics, 2002)
The author critiques the expedient application of market valuation principles by the transnational corporations and other large firms in the Indian pharmaceutical industry on a number of issues like patents, pricing, irrational drugs, clinical trials, etc. He contends that ethics in business is chiseled and etched within the confines of particular social structures of accumulation. An ascendant neo-liberal social structure of accumulation has basically shaped these firms' sharp opposition to the Indian Patents Act, 1970, government administered pricing, etc. The author contends that the practice of neo-liberal economics is strongly associated with a "one dimensional" ethics that privileges market valuation principles over all others. This seems to inevitably generate a social counter-movement that struggles for social protections. He critiques neo-liberal business practices from a perspective that derives from the work of the economic anthropologist Karl Polanyi. Before the present phase of liberalization in India, markets were "managed", but without a "welfare state" in place. Moving toward deregulation of the markets without a welfare state in place is unethical. Keeping the debilities of the institutional framework of public policy in mind, the author adopts a Polanyian perspective that places its trust and hope in the growing social legitimacy of the counter-movement in opposition to both neo-liberal business practices and the degenerate behavior of state agencies.
Political Science; Economics
Keywords: India; business ethics; intellectual property; international business enterprises; pharmaceutical industry; socialism

The Construction of Market Institutions in Russia: A View from the Institutionalism of Polanyi - Sánchez-Andrés, Antonio; March-Poquet, José M. (Journal of Economic Issues, 2002)
This article presents information on the construction of market institutions in Russia and includes the institutional conception provided by analyst Karl Polanyi. Polanyi's main ideas will be expounded in regard to his interest in analyzing the transition. These ideas will be adapted to the object of study and then specified so that they will be efficient criteria for analyzing the present economic transition. Second, the results obtained will be applied to the Russian case, and an attempt will be made to draw some conclusions about whether Russia is moving toward a market economy. Although several distinct parts of the work of Polanyi may be of great interest in analyzing the transition process that is occurring in countries that until the 1990s were organized by central planning.. This paper discusses only the aspects which are most closely related to the construction of market economies will be mentioned. According to Polanyi, the commercialization of productive factors and money are among the determining elements for the construction of an economic market.
Economics
Keywords: Russia (federation); analysts; central planning; economic reform; industrialization; markets; transition economies